Priming Effect of Colour on Aiding the Attentional Reorientation in Sequential Presentations of Temporal Data Visualization: Evidence From Eye-Tracking. Issue 2 (28th August 2021) - Peng, Ningyue; Xue, Chengqi; Wang, Haiyan; Niu, Yafeng; Wu, Lei
Abstract: In the present study, we focus on the priming effect of colour on mitigating the attentional reorientation cost, which is led by re-constructing the frame of reference for attention shift and visual search in sequential presentations of temporal data visualization. The study involves two experiments using complementary recordings of behavioural performance and eye-tracking events. Two aspects of colour primes are highlighted: the prime validity and the colour perceptual accessibility. A task paradigm integrating the feature search and keeping-track task was adopted in our experiments. In Experiment 1 (with a group of 16 participants), we confirmed the colour priming effect by comparing the priming condition to the neutral baseline. Furthermore, global colours that are with high perceptual accessibility generated more evident priming effects than local colours. However, more interferences in misguiding the attention to task-irrelevant regions were found when the global primes were invalid. In Experiment 2 (with another group of 15 participants), we verify the finding in Experiment 1 that global colours produced more pronounced priming effects in alleviating the attentional reorientation cost by comparing two groups of real-world visualizations with either global or local colours as the prime. Large saccades were initiated much earlier, and the search efficiency got improved when provided with global colours. We conjecture that the facilitatory effect from global colours may stem from its benefit on the pre-attentive processing of the search field. The research findings provide evidence for utilizing colours as the primes in mitigating the attentional reorientation cost and accelerating visual search in sequential presentations.